2007
DOI: 10.1152/ajpendo.00423.2006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of insulin-stimulated clearance of plasma nonesterified fatty acids in humans

Abstract: Insulin increases plasma nonesterified fatty acid (NEFA) clearance in humans, but whether this is independent of change in plasma NEFA appearance is currently unknown. Nine nondiabetic men (age: 28 Ϯ 3 yr, body mass index: 27.2 Ϯ 1.7 kg/m 2 ) underwent euglycemic clamps to maintain low (LINS) vs. high (HINS) physiological insulin levels for 6 h. An intravenous infusion of heparin ϩ Intralipid (HI) was performed during 4 of the 6 h of the clamps (in the last 4 h at LINS and in the first 4 h at HINS), whereas sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…The choice of [U-13 C]palmitate as the NEFA tracer was based on the following: 1) palmitate, oleate, and linoleate are the most prevalent NEFA both in human plasma and in Intralipid, and they have similar plasma clearance rates in humans (14); 2) palmitate was previously used to trace total NEFA turnover in humans after oral fat intake (15,16); and 3) during iv infusion of heparin plus Intralipid infusion (HI) in humans, we have shown that NEFA appearance rates determined with [U-13 C]palmitate predict very well the rates determined using simultaneous palmitate and linoleate tracers (r ϭ 0.90; P Ͻ 0.001) (17). To quantify plasma glycerol flux as a measure of whole body TG lipolysis, a primed continuous (1.6 mol/kg; 0.11 mol/kg ⅐ min Ϫ1 ) infusion of [1,1,2,3,3-2 H 5 ]glycerol (Cambridge Isotopes Laboratories) was also administered during both protocols (18).…”
Section: Experimental Protocolsmentioning
confidence: 63%
“…The choice of [U-13 C]palmitate as the NEFA tracer was based on the following: 1) palmitate, oleate, and linoleate are the most prevalent NEFA both in human plasma and in Intralipid, and they have similar plasma clearance rates in humans (14); 2) palmitate was previously used to trace total NEFA turnover in humans after oral fat intake (15,16); and 3) during iv infusion of heparin plus Intralipid infusion (HI) in humans, we have shown that NEFA appearance rates determined with [U-13 C]palmitate predict very well the rates determined using simultaneous palmitate and linoleate tracers (r ϭ 0.90; P Ͻ 0.001) (17). To quantify plasma glycerol flux as a measure of whole body TG lipolysis, a primed continuous (1.6 mol/kg; 0.11 mol/kg ⅐ min Ϫ1 ) infusion of [1,1,2,3,3-2 H 5 ]glycerol (Cambridge Isotopes Laboratories) was also administered during both protocols (18).…”
Section: Experimental Protocolsmentioning
confidence: 63%
“…RaNEFA was measured using i.v. administration of [U-13 C]-palmitate during protocol B using the Steele steady-state equation, as previously described (29,35). Tissue oxidative metabolism was determined after i.v.…”
Section: Methodsmentioning
confidence: 99%
“…ATBF after a normal meal peaks earlier than plasma TG levels (167). Similarly, lipoprotein lipase (LPL) action concomitantly with adipose tissue fat deposition occurs later (32,35). Conversely, ATBF coincides with FFA suppression (42), suggesting that increased postprandial blood flow might serve to deliver a signal, such as insulin, triggering postprandial LPL transcription in preparation for a subsequent peak in plasma TG.…”
Section: ·Minmentioning
confidence: 99%